TINJAUAN YURIDIS PENETAPAN BATAS BIDANG TANAH DI KABUPATEN KLATEN - SARJONO, SARJONO (Dinamika Hukum, 2015)
The purpose of the research is to review and to analyze delimitation plot based on Government Regulation No.24 year 1997 in the district of Klaten and obstacles faced in the implementation of delimitation plot conducted by measuring officer. The background of delimitation plot activity is often to have difficulties in the field, so it may cause a delay of delimitation plot activity. It needs officer’s accuracy in conducting delimitation plot and it also may cause spacious differences in certificate even though that the certificate contains legal certainty of land rights namely the limit, location, and spacious. Keyword : Delimitation Plot Based